Effects of the Decentralization of the Expenditure Execution Process on Municipal Public Spending - dos Santos, Dinah Vieira (2024)
This research uses a qualitative approach to investigate how the decentralization of budget execution of municipal expenditure affects public spending from the perspective of Public Choice Theory. The topic is relevant because it addresses the effects of organizational practice in the public sector with the potential to affect government spending. Multiple case studies were carried out with four medium-sized municipalities in the state of São Paulo, whose data were collected through semi-structured interviews following the within-case analysis pattern. The results demonstrate that the decentralization of the expenditure execution stages promoted gains in operationalizing the spending in areas whose budgetary management is complex, affecting both the quality and the level of municipal spending. This research also shows (i) the steps of commitment, liquidation, and payment as decision points on the spending; (ii) the type of resource managed by the areas as a factor of complexity in management; and (iii) the cost of decentralization and the lack of quality information systems as obstacles for municipalities to opt for decentralization. It concluded that the decentralization of expenditure execution affects public spending. Still, it is not an option applicable to any context since its viability and convenience depend on the characteristics of each municipality and its areas of government activity. It is also necessary to consider the self-interested behavior of the manager who has the power to decide on spending.